Parietal connectivity mediates multisensory facilitation - Brang, David (2013)
Our senses interact in daily life through multisensory integration, facilitating perceptual processes and behavioral responses. The neural mechanisms proposed to underlie this multisensory facilitation include anatomical connections directly linking early sensory areas, indirect connections to higher-order multisensory regions, as well as thalamic connections. Here we examine the relationship between white matter connectivity, as assessed with diffusion tensor imaging, and individual differences in multisensory facilitation and provide the first demonstration of a relationship between anatomical connectivity and multisensory processing in typically developed individuals. Using a whole-brain analysis and contrasting anatomical models of multisensory processing we found that increased connectivity between parietal regions and early sensory areas was associated with the facilitation of reaction times to multisensory (auditory-visual) stimuli. Furthermore, building on prior animal work suggesting the involvement of the superior colliculus in this process, using probabilistic tractography we determined that the strongest cortical projection area connected with the superior colliculus includes the region of connectivity implicated in our independent whole-brain analysis.